Bank Flows and Basel III—Determinants and Regional Differences in Emerging Markets - Ghosh, Swati; Sugawara, Naotaka; Zalduendo, Juan (World Bank, Washington, DC, 2012)
The global financial crisis has led to a range of reform proposals concerning the regulatory framework governing the banking sector collectively referred to as 'Basel III.' Although the proposed reforms are expected to generate substantial benefits by reducing the frequency and intensity of banking crises, concerns have been raised that, in the short term, the costs of moving to higher capital ratios may lead banks to raise their lending rates and reduce lending. This note explores the near-term implications of Basel III capital regulations on bank flows to emerging markets, based on an analysis of the key determinants of these flows.